Pola Komunikasi di Media Sosial dan Dampaknya terhadap Hubungan Sosial antar Perguruan Pencak Silat di Madiun - Yusron Badri; Sun Fatayati (Indonesian Journal of Humanities and Social Sciences, 2023)
Communication is essential not only in personal communication but also in organizational and group contexts. Organizational communication occurs vertically, horizontally, and across channels. The Paguyuban Kampung Pesilat in Madiun is a way to build social ties. It has been approved by 14 pencak silat colleges in the city and supported by the government and TNI/POLRI security forces. Pencak silat is one of the nation's cultural treasures that must be preserved. Even pencak silat itself has contributed to the process of Indonesian independence. This research aims to: (1). what is the communication pattern on social media towards social relations between martial arts colleges? (2). what is the impact of social relations between martial arts colleges on social media and in the real world? This research aims to find out the communication patterns of social relations between martial arts colleges on social media. The research methodology used is a qualitative explanation which aims to explain the position of the variables studied and the relationship between one variable and another. In contrast, the data collection techniques used are interviews, document studies, observations and literature studies. The theory used is the theory of organizational communication Horrison and Doerfel, Persuasive Communication and S-O-R Theory Studies. It can be said through the theory's assumption that "Communication is a key variable that makes it possible to build relationships in an organization and interact and share information". The results of this study indicate that organizational communication has a vital role in improving social relations between martial arts colleges in Dimadiun. The pattern of organizational communication towards martial arts colleges in Madiun is the formation of a paguyuban kampung pesilat as a place to improve social relations and efforts to overcome conflicts that continue to occur every year.